Alginate based Nanoparticles and Its Application in Drug Delivery Systems (Journal of Pharmaceutical Negative Results, 2022)
Nanoparticulate systems made of biopolymers encompass promising properties as carriers and adjuvant for drug delivery. Alginate is one of the most widely investigated biomaterials in the field of nanoparticulate drug delivery due to its biodegradability, biocompatibility, and bioadhesivity. Alginate nanoparticles for drug delivery can be prepared through spray drying, ionic gelation, emulsification, covalent cross-linking, polyelectrolyte complexation, self-assembling, etc. Alginate is an extensively utilized biopolymer in multiple applications due to its gelling property and chemical structure with hydroxyl and carboxylate moieties. The biocompatibility, biodegradability of alginate, and solubility in water have broadened up research perspectives in material, and biomedical sciences. Study of alginate-based nanoparticles, nanoaggregates, and nanofibers initiated recently. In the present review, the physicochemical properties of alginate, which enabled its use as a pharmaceutical excipient and as nanocarriers in drug delivery, have been reviewed. A special insight has been given on the modern advances of alginate nanoparticles in drug delivery and drug targeting applications. Besides this, limitations of alginate as nanocarriers in drug delivery and the future perspectives on how to augment utilization in the pharmaceutical nanotechnology have also been reviewed.